Níveis de contaminação no solo e na água decorrentes do uso de efluentes em perímetro urbano - Dantas, Tarcisio Batista (Universidade Federal Rural do Semi-Árido, 2012)
The quality of wastewater constitutes itself as a major limitation for agricultural production, lacking research to assess their sustainable reuse. The reuse in agriculture is pointed to by experts as an effective way to the final destination of wastewater. The technique available in the soil surface has been studied as a promising alternative for fodder production. In this sense, objective of this study was to characterize the effluent from urban sewage and evaluate the contamination levels of organic compounds and heavy metals in soil planted with elephant grass irrigated with wastewater in the outskirts of Caicó / RN. This study was conducted in the peripheral zone of Caicó. Being an area irrigated with river water free from sewage upstream of the city, called the reference area (RA), and three areas located downstream in areas irrigated with wastewater for 20, 36 and 48 years in the cultivation of elephant grass. t each site was demarcated a portion of 25x25m where randomly collected soil samples at depths 0-5, 5-20, 20-40 and 40-60 cm with three replicates in the months of julho/10, and dezembro/10 maio/11. The water sampling was conducted during the dry season in July, October and May and setembro/11 dezembro/10 and the local water catchment from urban wastewater for irrigation. The parameters analyzed in the water were: EC and pH at the collection site, Na+, K+, Ca2+, Mg2+, Cl-, Zn, Cu, Fe, Mn, Cd, Pb, Cr, Ni and P (total), N (Kjedhal ), NH3-N, and COD, BOD and fecal coliforms. And the soil analyzed as Cr, Cd, Ni, Pb, Zn, Cu, Mn, Na, K, N and P in addition to the MO, CE and pH. The wastewater monitoration the risk of toxicity showed moderate to high, middle class and high salinity with low concentration of heavy metals and BOD and coliform density above the standard recommended by CONAMA. Depths of 0 to 5 and 5 to 20cm of soil from areas irrigated with wastewater showed a significant difference. In general, the release of sewage into the soil during the dry season increased the concentration of organic and inorganic nitrogen in the soil compared to the local HR, high removal was observed after the rainy season. In general, the quality of wastewater no risk of adverse environmental impact if application techniques appropriate for water of inferior quality. Showing that reuse is a viable alternative source of water for forage production, especially in semi-arid climate region like Northeast Brazil.
Contamination levels in soil and water resulting from the use of wastewater in urban perimeter.
Keywords: Salinidade; Heavy Metais; Organic Matter; Removal; Salinidade; Metais Pesados; Metéria Orgânica; Remoção; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO